The effectiveness of emotion-focused therapy on the dark triangle of personality, high-risk sexual behaviors, and behavioral activation / inhibitory brain systems (BAS / BIS) in adolescents - Shirooyeh, Rozbeh; Khorsand Nobahar, Behnood (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2022)
More than any other group, adolescents engage in a wide range of risky behaviors that can be costly for them, their families, and their communities. High-risk behaviors are potentially destructive behaviors that individuals commit intentionally or unaware of adverse individual and social consequences. In other words, high-risk behaviors are behaviors that endanger people’s health and well-being. High-risk behaviors include a range of behaviors. The main purpose of this study was the effectiveness of emotion-focused therapy on the dark triangle of personality, high-risk sexual behaviors and behavioral activation / inhibitory systems (BAS / BIS) in adolescents referred to DIC centers in Tehran. The research method was quasi-experimental and the design used was pre-test post-test with a control group. The statistical population of the study included adolescents referring to vulnerability reduction centers and night shelters in Tehran in the second 6 months of 1399. Using the available sampling method, 30 people were selected and randomly divided into experimental and control groups Each group (15 people) were assigned. The measuring instruments were the Short Dark Traits of Personality Questionnaire (Johnson and Webster, 2010), the High-Risk Sexual Behaviors Questionnaire (Zarei et al., 2010) and the Inhibition / Behavioral Activation System Scale (Carver and White, 1994). Emotion-focused therapy was performed on the experimental group for 8 sessions of 90 minutes. The results of multivariate analysis of covariance showed that emotion-focused therapy had an effect on reducing the three dark symptoms of personality disorder, high-risk sexual behaviors, and behavioral activation / inhibition systems